THE MEASUREMENT OF EFFICIENCY AND FACTORS THAT AFFECT INDONESIA SHARIA INSURANCE EFFICIENCY - Fauziah, Nirwana; Mulyati, Heti; Ermawati, Wita Juwita (Universitas Brawijaya, Indonesia, 2020)
This study examines the efficiency level of Sharia Insurance in Indonesia from 2014 to 2017. In addition, to the factors that influence the efficiency of Sharia Insurance companies. Identifies of measurements using the DEA (Data Envelopment Analysis) method, the efficiency mean (x) of Sharia General Insurance results is higher than Sharia Life Insurance. The efficiency of Sharia General Insurance is at 82% categorized as high efficiency, whereas Sharia Life Insurance is at 75% and categorized as a medium efficiency. After obtaining the Sharia General Insurance and Sharia Life Insurance efficiency the variable was analyzed using the Tobit regression method with solvency ratios variable and company size. After partial processing, the results show that the solvency ratio has a negative and not significant effect while the size of the company's variables has a positive and not significant effect on Sharia General Insurance. In Sharia Life Insurance the solvency ratio variable influences negatively and is not significant. Whereas the size of the company is also positive and insignificant. After that, in the third stage to study non-financial factors that improve efficiency, the questionnaire was distributed to 50 respondents and processed using multiple linear regression models with variable Y, the efficiency and variable X, Technology, and Innovation. The results find that technology variables did not affect efficiency while innovation significantly increases efficiency. The higher the level of innovation, the higher the level of company efficiency.